Migration, Fear, Prejudice, and Manipulation - Ćirić, Jovan; Drndarević, Nikola (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
Migration of peoples is a theme that is contemporary not only in Serbia, but in the whole of Europe. The authors consider the implications of migrations in this article. The theme of migrations can be approached from different perspectives: juridical, sociological, economic, demographical, as well as the psychological perspective that Ciric and Drndarevic chose to analyse, considering migrants and their migrations. Authors are using the term ‘barbarians’, a term traditionally in use and in close relation to racist prejudices that exist in Western European civilisation. The history of raising walls that different empires used to defend from unwanted migrants and barbarians is also mentioned in the article. The frontier of the article concerns fears and prejudices, primarily as psychological phenomena, as well as relevant sociological, political and juridical meanings. Fear of the unknown peoples and unknown cultures, i.e. unknown migrants possesses in itself a considerable sociological, criminalistic and political relevance. The importance of prejudices is raised, as well as their social significance. Division between ‘us’ and ‘them’, fear of the unknown, of the barbarians and terrorists, and prejudices, open up the terrain for facilitated media manipulation. Several examples of media manipulation characteristic of anti-Serbian media hysteria at the end of the 20th century are also analysed. The mentioned manipulation and the resultant hysteria were based on certain psychological and political patterns, many of which are still characteristic of the current treatment of migrants, i.e. the treatment of barbarians and terrorists – the way migrants are perceived and treated in the Western public.